2004
DOI: 10.1521/pedi.18.1.3.32773
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Cognitive Analytic Therapy to the Treatment of Borderline Personality Disorder

Abstract: This article describes ways the theory and practice of cognitive analytic therapy (CAT) can contribute to the treatment and management of patients with borderline personality disorder (BPD). CAT, as its name suggests, was derived initially from an integration of conventionally opposed models. From the beginning, it was delivered within a limited timeframe, usually of 16 weekly sessions, extended to 24 in the case of more disturbed patients. Over time, on the basis of clinical experience, conceptual debate, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
135
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(139 citation statements)
references
References 36 publications
1
135
0
3
Order By: Relevance
“…Ryle's commentary on Holmes' reappraisal of AT (Holmes, 1994;Ryle, 1995b) criticized AT for its failure to acknowledge fully the central importance of such jointly created signs in human development, drawing on Leiman's (1992) reworking of ideas from Winnicott, Vygotsky and Bakhtin (see also Ryle, 1997b). Ryle's (1995b) paper also contrasted AT unfavourably with recent developmental psychology research into 'intersubjectivity', (e.g.…”
Section: The Place Of At In Current Cat Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ryle's commentary on Holmes' reappraisal of AT (Holmes, 1994;Ryle, 1995b) criticized AT for its failure to acknowledge fully the central importance of such jointly created signs in human development, drawing on Leiman's (1992) reworking of ideas from Winnicott, Vygotsky and Bakhtin (see also Ryle, 1997b). Ryle's (1995b) paper also contrasted AT unfavourably with recent developmental psychology research into 'intersubjectivity', (e.g.…”
Section: The Place Of At In Current Cat Thinkingmentioning
confidence: 99%
“…The current Guy's Hospital borderline protocol (Ryle, 1997b) involves four follow-up sessions extended over 6 months, after an initial 16-24 weekly sessions. Perhaps, with some of the most damaged patients, a model not unlike that described by Byng-Hall (1999) could be employed.…”
Section: Attachments and Time-limits In Cat Therapymentioning
confidence: 99%
“…To our knowledge, there are only two interventions thus far studied in borderline youth. Cognitive analytic therapy (CAT) (Ryle, 2004) was developed for the treatment of adults with BPD. CAT consists of 16-24 weekly individual sessions and uses elements of psychoanalytic object relations theory and cognitive psychology.…”
Section: Introductionmentioning
confidence: 99%
“…16 The psychological therapies with some evidence to demonstrate their effectiveness include: dialectical behaviour therapy; 6,17 therapeutic communities; 18 psychodynamic psychotherapies; 19 mentalisationbased therapy; 5 cognitive analytic therapy; 20 and cognitive behavioural therapy. 21 Studies on the effectiveness of these treatments have reported improvements in terms of reduced suicide attempts and selfharm behaviours, reduced use of a range of health services and reduced readmission rates to psychiatric wards.…”
Section: What Treatments Are Available?mentioning
confidence: 99%